Pengaruh Brand Image dan Gaya Hidup terhadap Keputusan Pembelian Ulang Iphone dengan Kepuasan Konsumen Sebagai Variabel Moderating di Mojokerto - Yuliana Putri, Afrianty; Setyariningsih, Eny; Hidayat, M. Syamsul (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In the current era of information technology development, product competition in the smartphone manufacturer market is increasingly rapid. Humans are also very dependent on technology, including smartphones. So manufacturers are working hard to meet these needs by producing various smartphones, one of which is the Apple iPhone. This research aims to determine the influence of brand image and lifestyle on iPhone repurchase decisions with consumer satisfaction as a moderating variable. This research uses a quantitative approach with the iPhone consumer population in Mojokerto. The sample was 200 respondents with a questionnaire as data collection and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) 4.0. The results of the research show that brand image positively and significantly influences repurchase decisions, lifestyle positively and significantly influences repurchase decisions, consumer satisfaction and repurchase decisions have a significant and positive influence, consumer satisfaction has a positive and significant effect in moderating brand image on decisions repeat purchases, consumer satisfaction has a positive and significant influence in moderating lifestyle and repurchase decisions.